Ashes2Art Now and Tomorrow: Delphi, Alexandria and the Red Sea - Arne R. Flaten (Virtual Archaeology Review)
Ashes2Art is a collaborative undergraduate research initiative focused on the application of digital tools to cultural heritage projects. The program started in 2005 at Coastal Carolina University, and from 2007 to 2009, Coastal Carolina University worked with students and faculty at Arkansas State University to study and build various digital resources pertaining to Delphi, Greece. In January 2011 the Ashes2Art project at Coastal Carolina University begins collaboration with the Center for Maritime Archaeology and Underwater Cultural Heritage at Alexandria University, Egypt. We will work with excavation directors on Lake Mareotis (near Alexandria) and at various sites along the Red Sea.